2003
DOI: 10.1097/00061198-200304000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Open-Angle Glaucoma: Variations in the Intraocular Pressure After Visual Field Examination

Abstract: Intraocular pressure varied significantly and tended to increase immediately after automated visual field examination in patients with primary open-angle glaucoma. Age seemed to contribute to these IOP changes, but other factors could be involved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
28
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 17 publications
0
28
1
Order By: Relevance
“…Recupero et al 1 first reported a transient 1-hour increase in IOP of 2.38 mm Hg after VF testing in 94 POAG eyes. We report the first confirmatory study of these results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recupero et al 1 first reported a transient 1-hour increase in IOP of 2.38 mm Hg after VF testing in 94 POAG eyes. We report the first confirmatory study of these results.…”
Section: Discussionmentioning
confidence: 99%
“…We report the first confirmatory study of these results. Recupero et al 1 hypothesize that decreased accommodation with age may be a factor that reduces outflow facility. In our study, regression analysis shows no significant relationship between age and IOP variation after VF testing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect was most marked in elderly patients. 12 The maximum increase in IOP was 11 mm Hg. Lack of accommodation was proposed as one of many possible reasons for IOP increase after VF examinations.…”
Section: Introductionmentioning
confidence: 91%
“…Lack of accommodation was proposed as one of many possible reasons for IOP increase after VF examinations. 12 During the past decades, new examination algorithms and new perimetric techniques have been developed, with the specific aim to decrease examination time in order to increase quality and accuracy of the examination. The SITA algorithm for the HFA perimeter 13 and the high-pass resolution perimeter (HRP) 14 are examples of this attempt.…”
Section: Introductionmentioning
confidence: 99%